Cenozoic deformation and exhumation of the Kampot Fold Belt and implications for south Indochina tectonics. Issue 7 (12th July 2016) - Fyhn, Michael B. W.; Green, Paul F.; Bergman, Steven C.; Van Itterbeeck, Jimmy; Tri, Tran V.; Dien, Phan T.; Abatzis, Ioannis; Thomsen, Tonny B.; Chea, Socheat; Pedersen, Stig A. S.; Mai, Le C.; Tuan, Hoang A.; et al.
Abstract: Latest Mesozoic to earliest Cenozoic deformation affected SE Asia's Sundaland core. The deformation event bridges the Mesozoic SE Asian fusion with the Cenozoic era of rifting, translation, basin formation, and the creation of modern SE Asian oceans. Southern Cambodia and Vietnam are central to this shift, but geological investigations of the region are in their infancy. Based on apatite and zircon fission track analyses (AFTA and ZFTA), stratigraphic and structural observations, seismic data, thermal maturity, and igneous rock dating, the geological evolution of southern Cambodia and Vietnam is investigated. Diverse depositional styles, igneous activity, structural deformation and subsurface unconformities testify to a highly variable Phanerozoic tectonic setting. Major latest Cretaceous to Paleocene thrusting and uplift affected the Kampot Fold Belt and surrounding regions and the associated up to ~11 km exhumation probably exceeds earlier denudation events since at least Permian time. The present relief of the Bokor Mountains rising high above the Kampot Fold Belt represents an artifact after differential erosion and only 2.5–4.5 km of erosion affected this area. The latest Cretaceous to Paleocene orogenesis affected much of greater Indochina probably owing to plate collision along eastern Sundaland or a combination of collisions along both east and west Sundaland. AFTA and ZFTA data document protracted cooling of Cretaceous granites and locally elevated thermal gradients persisting a few tens of million years after their emplacement. The thermal gradient had stabilized by early Miocene time, and Miocene cooling probably reflects a renewed denudation pulse driven by either regional tectonism or climate‐enhanced erosion. Key Points: Paleocene orogenesis took place across most of Sundaland including south Indochina Kilometers of orogenic exhumation and structuring affected southern Cambodia and Vietnam Plate collision along the Sundaland margin most likely drove deformation